Kemampuan Pengurus Rayon Dalam Ta’bir Tahriri di Pondok Modern Darussalam Gontor (Studi Analisis Deskriptif) - Nurul Salis (At-Ta'dib, 2016)
Darussalam Modern Islamic Boarding School Gontor is Islamiceducational institutions with dormitory system oriented in the field ofeducation and cadreses of people formation. The method used by givingassignments in the dormitory as a manager of dormitory in DarussalamModern Islamic Boarding School Gontor, which functions as a regulator andcontroller for all student activities directionally. This research is intended todetermine the ability of dormitory managers of class four about writtenfabrication’s grade at Islamic Teacher Trainning Collage, Darussalam ModernIslamic Boarding School Gontor Ponorogo. Type of this research is field studythat is descriptive quantitative and comparative quantitative. This samplewas taken and determined by Stratified Random Sampling, becausecapabilities of each individual is different. Research data processing wascarried out by the statistic method. The result of this study was showed thatlevels of dormitory’s manager has good result for written fabrication’s. Theresults can be seen from the result that was gotten them in this lesson is 6.71which is divided the result from all of manager of class four, 42 people.